CORRELATION BETWEEN DIET PATTERN AND GINGIVITIS -A RETROSPECTIVE STUDY - V, Padmaharish; Ramamurthy, Jaiganesh; Gurunathan, Deepa (International Journal of Psychosocial Rehabilitation, 2025)
Gingivitis is the inflammation of gingiva most commonly caused due to plaque accumulation. Dental plaque is a complex biofilm accumulation on teeth and oral tissues. Diet seems to have a profound impact on the gingival and periodontal inflammatory reaction. It is important to create awareness about better nutritional interventions among the general population to prevent further progression of gingival disease. The aim of this study was to assess the correlation between diet pattern and gingivitis. A retrospective study was conducted using the case records of patients visiting a private dental college in Chennai from June 2019 - March 2020. The study population included case records of patients between 18 and 25 years of age with recorded gingival index scores, selected by non-probability purposive sampling. Data was collected and then subjected to statistical analysis. Microsoft Excel 2016 (Microsoft office 10) data spreadsheet was used to collect data and later exported to SPSS IBM (version 20.0). Descriptive statistics and chi square test were employed with a level of significance set at p0.05), though the prevalence and severity of gingival disease was increased among people with a nonvegetarian diet. There was a significant association between plaque index and gingival index scores (p=0.000), with the severity of gingivitis increasing as the plaque index score increases.